1979
DOI: 10.1007/bf01102878
|View full text |Cite
|
Sign up to set email alerts
|

Malignant giant cell tumor of tendon sheath

Abstract: A benign, but aggressive, giant cell tumor of tendon sheath developed over a period of 20 years into a metasasizing, histologiclly malignant giant cell tumor. Ultrastructure of the malignant tumor showed the same five cell types as described in giant cell tumors of tendon sheath. Even the same crystals were identified in the osteoblast-like and osteoclast-like cells. It therefore appears reasonable to assume that giant cell tumors of tendon sheath indeed are neoplasms with a malignant potential and not an infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0
3

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 8 publications
0
28
0
3
Order By: Relevance
“…This bone erosion is suggested to occur because of pressure from the soft-tissue mass (6). However, invasion and destruction of the adjacent bone matrix has been observed as well (8,11). Furthermore, GC derived from GCTTS have been shown to resorb bone (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bone erosion is suggested to occur because of pressure from the soft-tissue mass (6). However, invasion and destruction of the adjacent bone matrix has been observed as well (8,11). Furthermore, GC derived from GCTTS have been shown to resorb bone (12).…”
Section: Discussionmentioning
confidence: 99%
“…These erosions are suggested to occur because of pressure from the proliferative tissue (6). However, destruction of adjacent bone by an invasive tissue front has been observed as well (8,11). Furthermore, Athanasou et al (12) found that GC isolated from GCTTS demonstrated resorption pit formation when cultured on cortical bone slides.…”
mentioning
confidence: 99%
“…9 However, their capacity for a certain degree of autonomous growth, local recurrence if inadequately excised and rarely metastasis speaks strongly for a neoplastic theory. 4,16,17 Although histomorphologically similar, TGCT-D, TGCT-L and PVNS differ in their clinical and biologic behavior and should not be used as synonyms. 2,8,14 TGCT-L may occur at any age but is most often seen in the third to fifth decades with a slight female predominance, unlike the younger age group, which is affected in TGCT-D and PVNS.…”
Section: Discussionmentioning
confidence: 99%
“…Only 37 malignant tenosynovial GCTs have been reported in the literature since 1979, and these are summarized in ►Tables 1-3. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Of these 37 patients, follow-up outcome was known in 30 patients; one patient had died of other causes (DOC). Of the remaining 29 patients, 11 patients died of disease (DOD), 4 patients were living with disease (LWD) and 14 patients had no evidence of disease (NED) since their last treatment, with a follow-up of 6 months to 49 years.…”
Section: Discussionmentioning
confidence: 99%